Epidemiology of head and neck neoplasms: a review - Munjal, Manish; Kaur, Ramanpreet; Sharma, Sarit; Kaur, Raminderjit; Kailey, Vikramjit; Munjal, Shubham; Saggar, Tulika; Verma, Hitesh (International Journal Of Community Medicine And Public Health, 2020)
Head and neck malignancy is the sixth common type of cancer, representing about 6% of all cases and accounting for an estimated 6,50,000 new cancer cases and 3,50,000 cancer deaths worldwide every year. An overview of the problem with emphasis on its global epidemiology is being reviewed.